2021
DOI: 10.1371/journal.pone.0248771
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and behavioral features of acute hyperpurinergia and the maternal immune activation mouse model of autism spectrum disorder

Abstract: Since 2012, studies in mice, rats, and humans have suggested that abnormalities in purinergic signaling may be a final common pathway for many genetic and environmental causes of autism spectrum disorder (ASD). The current study in mice was conducted to characterize the bioenergetic, metabolomic, breathomic, and behavioral features of acute hyperpurinergia triggered by systemic injection of the purinergic agonist and danger signal, extracellular ATP (eATP). Responses were studied in C57BL/6J mice in the matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 161 publications
0
19
0
Order By: Relevance
“…Functionally, the P2Y1 receptor signaling pathway is one of the major purinergic signaling pathways that may contribute to altered astrocyte properties in neurodegeneration, especially in AD. P2Y1 mediates calcium waves in astrocytes, which are linked to gliotransmitter release and synchronization of astrocytic syncytium, which is critical for synaptic plasticity (149)(150)(151). Unlike in the transcriptomic studies we summarized here, previous studies showed that astrocytic P2Y1 receptor expression is elevated in AD mouse models and human AD brain, especially in close vicinity to amyloid plaques (151,152).…”
Section: Astrocytesmentioning
confidence: 58%
“…Functionally, the P2Y1 receptor signaling pathway is one of the major purinergic signaling pathways that may contribute to altered astrocyte properties in neurodegeneration, especially in AD. P2Y1 mediates calcium waves in astrocytes, which are linked to gliotransmitter release and synchronization of astrocytic syncytium, which is critical for synaptic plasticity (149)(150)(151). Unlike in the transcriptomic studies we summarized here, previous studies showed that astrocytic P2Y1 receptor expression is elevated in AD mouse models and human AD brain, especially in close vicinity to amyloid plaques (151,152).…”
Section: Astrocytesmentioning
confidence: 58%
“…A recent study aimed to characterize metabolomic features in hyperpurinergic conditions using a maternal immune activation mouse model. Fifty percent of plasma metabolites (202/401) from 37 pathways were altered significantly, with xanthosine, dopamine, and L-isoleucine ranked as the most altered metabolites in the maternal immune activation mice ( Zolkipli-Cunningham et al, 2021 ). A further study has focused on valproic acid-induced ASD rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reveals here lipidomic changes in the myelin-rich striatum in detail in the 16p11.2 ± ASD mouse model, highlighting decreased levels of key lipid components of myelin -CerG1, SM and Cer species -in 16p11.2 ± striatum (Figures 4-6). Interestingly, in the maternal immune activation (MIA) mouse model of ASD, where autism-like symptoms arise from acute hyperpurinergia, the plasma levels of 15 Cer and 15 SM species (most having a long acyl chain) have been shown to be significantly reduced (Zolkipli-Cunningham et al, 2021). Taken together, a commonality between these observations regarding ASD is altered lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%